Effect of iron and boron ultrafine powders on combustion of aluminized solid propellants; Combustion and Flame; Vol. 178 - Korotkikh A. G. Aleksandr Gennadievich; Glotov O. G. Oleg; Arkhipov V. A. Vladimir Afanasjevich; Zarko V. E. Vladimir Egorovich; Kiskin A. B. (2017, 2017)
Title screen